Semantic Web Related to ITS Systems - Pavel Pribyl; Vit Fabera; Vladimir Faltus; Lukas Tyfa (Communications - Scientific letters of the University of Zilina, 2013)
This paper describes a way to better navigate in an ever increasing number of standards in the field of ITS. Short overview about fundamental ITS models is presented, the principles of related knowledge system are described. Ontology approach is used, especially as domain-oriented ITS ontology, where a new hybrid method is explained.